Anastomotic Leak in Colorectal Cancer Surgery: From Diagnosis to Management or Failure - A Retrospective Cohort Study - Rama, Nuno (2021)
Anastomotic leakage (AL) after colorectal resections is a common surgical experience and the most frequent major adverse outcome. Early recognition of AL is critical to reduce mortality. We aim to evaluate the incidence, diagnostic criteria, morbidity, and mortality related with AL.